Comparison of the Effectiveness of Quizalize and Quizziz Learning Media on Children's Learning Outcomes at Al-Kautsar Kindergarten in Bengkulu City - Fatimah Nur Faizah; Suhaimi; Aura Frasischa; Muhammad Hafiz Kurniawan; Nina Kurniah (Indonesian Journal of Pedagogy and Teacher Education, 2025)
Background: As technology has advanced, educational tools have seen numerous transformations, notably the introduction of game-based platforms like Quizizz and Quizalize. Both media offer interactive approaches to improve learning outcomes. These media can be used in kindergarten learning, but there has been no study comparing their effectiveness in kindergartens in Bengkulu. Aims: To compare the effects of Quizalize and Quizizz media on children's learning outcomes. Methods: Quasi-experiment with 30 students (15 experimental class, 15 control class). Analysis using normality test, homogeneity test, t-test, and Normalized Gain (N-Gain). Results: There was no significant difference in the pre-test (p = 0.936), but the post-test showed a significant difference (p = 0.020). However, when compared based on N-Gain, there was no significant difference between the two media (p = 0.282). Conclusion: These findings indicate that both Quizalize and Quizizz are equally effective in improving children's learning outcomes. There are no statistical findings to support the superiority of either medium.